Bearing Fault Monitoring Using CWT Based Vibration Signature. (2016) - Saxena, Madhavendra; Bannet, Olvin Oliver; Gupta, Manoj; Rajoria, R.P.
Abstract: This paper introduces a new approach for generating patterns of phenomena associated with vibration of bearing faults using continuous wavelet transform (CWT). These patterns may be used as signatures for identification of bearing faults. There are four types of bearing faults namely inner race fault, outer race fault, ball fault and cage fault. This work is carried out for inner race and outer race faults. The signatures obtained are found to be unique for a particular type of bearing fault and can be used for identification of bearing faults.